2010
DOI: 10.1021/ma1020903
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Long-Chain Highly Branched Polymers via One-Pot Tandem Ring-Opening Metathesis Polymerization and Acyclic Diene Metathesis Polymerization

Abstract: A facile one-pot synthesis of long-chain highly branched polymers (LCHBPs) was accomplished by a tandem ring-opening metathesis polymerization (ROMP) and acyclic diene metathesis (ADMET) polymerization procedure. A telechelic polymer with two terminal allyloxy groups and many pendent acrylates was first prepared through the first generation Grubbs catalyst-mediated chain transfer ROMP of 7-oxanorborn-5-ene-exo,exo-2,3-dicarboxylic acid bis(2-(acryloyloxy)ethyl) ester in the presence of a symmetrical multifunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 74 publications
0
57
0
Order By: Relevance
“…Moreover, the macromonomer approach to make LCHB polymers is unique in being able to make hyperbranched block copolymers, HyperBlocks, exemplified in the production of an ABA triblock copolymeric macromonomer of polyisoprene-polystyrene-polyisoprene and first reported by ourselves in a proof of concept study 54 . In recent years the 'macromonomer' approach to make LCHBPs has been widely adopted with reported examples of macromonomers produced by ring opening metathesis polymerization (ROMP) [56][57][58][59] , reversible-addition chain transfer polymerization (RAFT) 60,61 , atom transfer radical polymerization (ATRP) [62][63][64][65][66] In the proof of principle study in which the concept of HyperBlocks was first reported 54 , a single sample of a HyperBlock was synthesised and analysed by TEM and tensile testing to obtain information about the influence of architecture on solid-state morphology and mechanical properties. The macromonomer used in this case was an ABA triblock copolymer of polystyrene and polyisoprene with chain-end functionalities, phenol and bromide, to enable a Williamson coupling reaction for the synthesis of the HyperBlock.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the macromonomer approach to make LCHB polymers is unique in being able to make hyperbranched block copolymers, HyperBlocks, exemplified in the production of an ABA triblock copolymeric macromonomer of polyisoprene-polystyrene-polyisoprene and first reported by ourselves in a proof of concept study 54 . In recent years the 'macromonomer' approach to make LCHBPs has been widely adopted with reported examples of macromonomers produced by ring opening metathesis polymerization (ROMP) [56][57][58][59] , reversible-addition chain transfer polymerization (RAFT) 60,61 , atom transfer radical polymerization (ATRP) [62][63][64][65][66] In the proof of principle study in which the concept of HyperBlocks was first reported 54 , a single sample of a HyperBlock was synthesised and analysed by TEM and tensile testing to obtain information about the influence of architecture on solid-state morphology and mechanical properties. The macromonomer used in this case was an ABA triblock copolymer of polystyrene and polyisoprene with chain-end functionalities, phenol and bromide, to enable a Williamson coupling reaction for the synthesis of the HyperBlock.…”
Section: Introductionmentioning
confidence: 99%
“…However, as far as we are concerned there are comparatively few pathways toward HBP structures have been described to date [16][17][18][19][20][21]. Grubbs and others reported [16][17][18][19][20] a relatively simple method for the synthesis of HBPs using a new step condensation polymerization, acyclic diene metathesis (ADMET) polymerization of easily synthesized AB 2 monomers under mild conditions in conjunction with ruthenium-based catalysts. The great advantage of this method is that HBPs are synthesized in one pot instead of tedious step-by-step process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Xie originated a facile approach named tandem chain transfer ROMP and ADMET polymerization for synthesizing long-chain, highly branched polymers in a one-feed procedure. [ 12 ] Recently, this group utilized one-pot ROMP and head-to-tail ADMET polymerization to prepare linear-hyperbranched copolymers with a two-feed procedure. [ 13 ] When compared to the one-feed procedure, the two-feed procedure usually allowed for better synthetic control over the resulting polymers.…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ] Then the molecular weights of 3b and 3c were determined. GPC ( Figure S6 and S8, Supporting Information) and 1 H NMR analysis ( Figure S4a and S7a, Supporting Information) indicated that all the molecular weight data for 3b and 3c…”
Section: Polymer T [H] Yield A)mentioning
confidence: 99%